ENVIRONMENTAL SERVICES CARBON STOCK OF TREE ON GREEN BELT ON JENDERAL SUDIRMAN STREET, SUKOHARJO DISTRICT - Sarwendah Dwi Juniati; Dhea Gita Fitri Sagitarian; Ilhamnul Zain Satria Negara (Yayasan Nusantara Hasana Berdikari, 2023)
Trees have capabilities in environmental services related to carbon stocks. Green belts along urban roads have the function of absorbing CO2 in the air needed for the photosynthesis process, with the result in the form of carbohydrates for growth, and the rest is buried in the form of carbon. This study was conducted to determine the carbon stocks of tree on the green belt on the side of Jenderal Sudirman Street. This study was conducted in May 2023 on Jenderal Sudirman Street in front of the Menara Wijaya Building and Sukoharjo District Head Office. Data was collected using the diameter census method on each tree. Data was analyzed using allometric equations to calculate biomass values and carbon stock equations to determine carbon stock values. The results showed that on the green belt, as many as eight species of trees were found, with 67 individual trees. The most widely planted species on the green belt is Pterocarpus indicus Willd. (Angsana) with a total of 33 individuals. The highest biomass value owned by the species Pterocarpus indicus Willd. (Angsana) at 0.79874 tons. The highest carbon stock value owned by the species Pterocarpus indicus Willd. (Angsana) at 0.39937 tons.